Rethinking responses towards group-homes: inclusionary legislation, supportive municipal attitudes, and place-based opposition. (24th March 2019) - Singer, Matan E.; Rosen, Gillad
Abstract: Little research has been devoted to uncontested human services facilities, nor to the legal frameworks siting proposals are situated in. To address these, this paper examines group-homes that operated in Jerusalem, Israel, between 2002 and 2012, identifies and explores a range of responses group-homes encounter. Results point to only low levels of opposition alongside a relatively equal distribution of group-homes across all areas of the city, including affluent neighbourhoods. Interviews with key stakeholders suggest that these results have been the outcome of a combination of inclusionary national legislation, supportive municipal attitudes and actions, and a proactive approach adopted by service-providers. Through focusing on existing group-homes we find that the characteristics of opposition depend, in part, on the stage of the group-home's life cycle in which it occurs. Specifically, opposition occurring in the pre- and upon-siting stages resemble typical NIMBY opposition while those occurring post-siting are more place-based. These results point to the importance of examining opposition within the context of inclusionary legislation, municipal attitudes and place-based responses.